Fine art painting Between the intellectual imaginary and the stylistic verifier (An analytical study) (Journal of the College of Basic Education, 2022)
The study tagged (the plastic art painting between the intellectual imaginary and the stylistic verifier) ​​represents a scientific effort to reveal the ability of the artistic method and the method technique in embodying the artist's ideas and mental perceptions - artistically - through the process of artistic formation. As well as revealing the reference of the relationship between the artist's imagination and the process of intellectual coding employed - stylistically - within the artwork (or plastic painting). This results in the researcher collecting scientific materials to serve the subject of the research in three chapters..The first chapter included the methodology of the research (the problem of the research, its importance, objectives and limits, and defining the most important terms included